Representation of Kimberle Crenshaws intersectionality in the novel Rara Mendut by Y. B. Mangunwijaya - Sri Lestari; Retno Winarni; Sumarwati Sumarwati (Universitas Syiah Kuala, 2025)
Intersectionality studies are gaining increasing attention in the humanities and literary research, especially in the context of feminist literary analysis and gender studies. This research aimed to describe the representation of intersectionality in the novel Rara Mendut by Y. B. Mangunwijaya. The research method used was descriptive qualitative, guided by Kimberle Crenshaws intersectionality theory. The data in this study were collected using reading and writing techniques and analysed using content analysis. The results demonstrated that, in the context of structural intersectionality, the novel depicted the complex layers of Rara Menduts identity, including age, gender, social class, and economic conditions. Rara Menduts experiences reflected inequality and the exploration of gender identity at a young age, while her mothers economic condition and widow status showed the impact of social class. Political intersectionality was reflected in Rara Menduts marriage demands, which reflect the social and political norms of the time. This highlighted how womens identities were trapped within power structures and social norms. Representational intersectionality was seen in Rara Menduts achievements as a symbol of victory for women. The character of Nyai Ajeng showed how womens intelligence and beauty could transcend gender stereotypes, but are constrained by traditional expectations. The analysis of intersectionality in the novel offers perspectives into the complexity of individual experiences. Understanding the interconnectedness of identities is necessary for designing more inclusive solutions and policies in society. This research contributes to the understanding of intersectionality in a literary context, supporting efforts towards a more just and inclusive society.